The Effectiveness of MOOCs on Learning Outcomes in Energy Training: An Evaluation Based on the Kirkpatrick Model - Pulungan, Zainul (Monas: Jurnal Inovasi Aparatur, 2025)
This study evaluates participant responses to energy-sector training delivered through a Massive Open Online Course (MOOC), measures the resulting learning outcomes, and analyzes the influence of participant reactions on those outcomes. The research employed a survey-based evaluation involving 121 participants of the MOOC GREEN Cohort III training at PPSDM KEBTKE. Data collection methods included questionnaires to assess participant reactions and tests to measure learning outcomes. Data were analyzed using descriptive statistics, paired sample t-tests, and simple correlation analysis. Findings indicate that overall participant responses were moderately positive, with an average score of 3.57 out of 4, although certain aspects—particularly platform design—require improvement. Pre-test and post-test results revealed a significant increase in learning outcomes, with an average gain of 17.73 points. Correlation analysis between pre-test and post-test scores showed a strong positive relationship. However, the correlation between participant responses and learning outcomes yielded a Sig. (2-tailed) value of 0.186, indicating a very weak relationship. The study concludes that MOOC-based training is effective in enhancing learning outcomes in the energy sector. Nevertheless, improvements in platform aesthetics and inclusivity are recommended to enrich the overall learning experience.